三角函数之积化和差公式(二)
Invoke: 和差化积公式
根据 和差化积 推衍出 积化和差
procedure
\[\begin{align}
序1:
已知和差化积公式:\\
\sin\alpha+\sin\beta=2\sin\frac{\alpha+\beta}{2}\cos\frac{\alpha-\beta}{2}
\\ \\
设\alpha\Rightarrow\alpha+\beta, \quad \beta\Rightarrow\alpha-\beta
\\ \\
\Rightarrow
\sin\left[ \frac{\left(\alpha+\beta\right)+\left(\alpha-\beta\right)}{2} \right]
\cos\left[\frac{\left(\alpha+\beta\right)-\left(\alpha-\beta\right)}{2}\right]
=\frac{\sin\left(\alpha+\beta\right)+\sin\left(\alpha-\beta\right)}{2}
\\ \\
\Rightarrow\sin\alpha\cos\beta=
\frac{\sin\left(\alpha+\beta\right)+\sin\left(\alpha-\beta\right)}{2}
\\ \\
获得公式1: \\
\sin\alpha\cos\beta=
\frac{\sin\left(\alpha+\beta\right)+\sin\left(\alpha-\beta\right)}{2}
\\ \\ \\
序2:
已知和差化积公式:\\
\sin\alpha-\sin\beta=2\cos\frac{\alpha+\beta}{2}\sin\frac{\alpha-\beta}{2}
\\ \\
设\alpha\Rightarrow\alpha+\beta, \quad \beta\Rightarrow\alpha-\beta
\\ \\
\Rightarrow\cos[\frac{(\alpha+\beta)+(\alpha-\beta)}{2}]\sin[\frac{(\alpha+\beta)-(\alpha-\beta)}{2}]
=\frac{\sin(\alpha+\beta)-\sin(\alpha-\beta)}{2}
\\ \\
\Rightarrow\cos\alpha\sin\beta=\frac{\sin(\alpha+\beta)-\sin(\alpha-\beta)}{2}
\\ \\
获得公式2: \\
\cos\alpha\sin\beta=\frac{\sin(\alpha+\beta)-\sin(\alpha-\beta)}{2}
\\ \\ \\
序3:
已知和差化积公式: \\
\cos\alpha+\cos\beta=2\cos\frac{(\alpha+\beta)}{2}\cos\frac{\alpha-\beta}{2}
\\ \\
设\alpha\Rightarrow\alpha+\beta, \quad \beta\Rightarrow\alpha-\beta
\\ \\
\cos\left[\frac{(\alpha+\beta)+(\alpha-\beta)}{2}\right]\cos\left[\frac{(\alpha+\beta)-(\alpha-\beta)}{2}\right]
=\frac{\cos\left(\alpha+\beta\right)+\cos\left(\alpha-\beta\right)}{2}
\\ \\
\Rightarrow
\cos\alpha\cos\beta=\frac{\cos\left(\alpha+\beta\right)+\cos\left(\alpha-\beta\right)}{2}
\\ \\
获得公式3: \\
\cos\alpha\cos\beta=\frac{\cos\left(\alpha+\beta\right)+\cos\left(\alpha-\beta\right)}{2}
\\ \\ \\
序4:
已知和差化积公式: \\
\cos\alpha-\cos\beta=-2\sin\frac{\alpha+\beta}{2}\sin\frac{\alpha-\beta}{2}
\\ \\
设\alpha\Rightarrow\alpha+\beta, \quad \beta\Rightarrow\alpha-\beta
\\ \\
\Rightarrow\sin[\frac{(\alpha+\beta)+(\alpha-\beta)}{2}]\sin[\frac{(\alpha+\beta)-(\alpha-\beta)}{2}]
=\frac{\cos(\alpha+\beta)-\cos(\alpha-\beta)}{-2}
\\ \\
\Rightarrow
\sin\alpha\sin\beta=\frac{\cos(\alpha+\beta)-\cos(\alpha+\beta)}{-2}
\\ \\
获得公式4: \\
\sin\alpha\sin\beta=\frac{\cos(\alpha+\beta)-\cos(\alpha+\beta)}{-2}
\end{align}
\]
Summarize
\[\begin{align}
\\ \\
公式1: \enspace
\sin\alpha\cos\beta=
\frac{\sin\left(\alpha+\beta\right)+\sin\left(\alpha-\beta\right)}{2}
\\ \\
公式2: \enspace
\cos\alpha\sin\beta=\frac{\sin(\alpha+\beta)-\sin(\alpha-\beta)}{2}
\\ \\
公式3: \enspace
\cos\alpha\cos\beta=\frac{\cos\left(\alpha+\beta\right)+\cos\left(\alpha-\beta\right)}{2}
\\ \\
公式4: \enspace
\sin\alpha\sin\beta=\frac{\cos(\alpha+\beta)-\cos(\alpha+\beta)}{-2}
\end{align}
\]